Growing Grief: Cultivating Life After Death in the Garden - Tynan Avril (Finland, 2025)
In this paper, I explore how cultural representations of gardens are entangled with stories of grief in productive and creative ways to demonstrate ongoing attachments and relationships with the dead. Building on the turn in grief and death studies towards a “continuing bonds” model, I argue that grief is enmeshed in the spaces and places of the past, present, and future, in relations between self and others, and in the social performance of private and public expectations. The garden is thus an ideal location in which to think about grief alongside perpetual return, persistence, and multiplicity as an activity of ongoing and future-oriented interaction with the deceased. In a range of cultural sources, including Hugo Simberg’s The Garden of Death (Kuoleman puutarha, 1896), Frances Hodgson Burnett’s The Secret Garden (1911), and Mélissa Da Costa’s Les Lendemains (2020) [The Days After], gardens and gardening feature alongside symbols and storylines of death and grief. In these works, the garden becomes a site for the construction and reconstruction of relationships between the living and the dead. Gardens, therefore, do not provide closure so much as open up avenues of communication and consolation to intertwine the living and the dead, the past, present, and future, and different places, spaces, and environments. In this paper, I show how grief, without any definitive endpoint, shapes and takes shape in the garden. In argue that there is an optimism to be found in the garden as a cultural site of grieving that does not signal detachment from the dead but employs loss as a productive and creative force for future-oriented growth and change.